A new model on recombination dynamics of polar InGaN/GaN MQW LED and IQE measurement. (31st March 2020) - Ma, Cang Min; Tian, Ming; Li, Peng; Mo, Jun Sen; Niu, Wen Long; Lin, Tao; Feng, Zhe Chuan
Abstract: Understanding the recombination nature in a polar InGaN/GaN multiple quantum well (MQW) light-emitting diode (LED) or similar device is critical for their further performance enhancements. This paper reports a new theoretical model for investigating the recombination dynamics in MQW LEDs, which more comprehensively takes both localized exciton recombination (LER) and free carrier recombination (FCR) into account. The obtained rates for LER, FCR and nonradiative recombination show a clear picture of recombination paths in a commercial blue MQW LED wafer. They can be also used to calculate the internal quantum efficiency without involving any extra measurements or prerequisites. This model may provide a universal solution to express the complicated recombination dynamics in various kinds of MQW LEDs.